From pain to purpose how to move on after loss - Jones, Jocelyn Singwey (John 14:14 Book Publishing Center, 2025)
"Grief is hard to deal with, but you don't have to face it alone. This book is here to be your companion on your path to healing. Through personal experiences, powerful insights, and practical principles, it offers comfort and guidance for those grieving a loss or supporting someone who is."--Back cover.